(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
Presented study aims to estimate the influence of Adaptive Statisti cal Iterative Reconstruction (ASIR) algorithm on dose reduction and images quality on Computed tomography (CT) Chest with contrast ex amination compared with the traditional Filter back projection tech niques (FBP). Patients were performed by two scanner using two reconstruction techniques, FBP in 28 patients and ASIR algorithm in 22 patients. Signal-to-Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR) were compared between FBP and ASIR images, CT im ages were tested on different percentage ASIR (0%, 30%, 50%, and 80%). Then, FBP and ASIR images were compared again. Computed tomography dose index volume (CTDIVOL) and effective doses (EDs) recorded simultaneously. Images quality parameters were estimated at the level of the carina in the descending thoracic aorta. Resulting data assessed by two techniques (FBP, ASIR) were compared statisti cally. The average image quality in FBP was superior to that of ASIR images. SNR were (16.50±5.91, 7.58±0.81BMI <30) (12.78±8.63, 8.37±3.51, BMI >30), CNR were (11.88±5.60, 5.35±0.94, BMI <30), (8.85±7.60, 5.39±2.72, BMI >30) for FBP, ASIR respectively. Signifi cant increase in the SNR and CNR was observed with increased per centage of ASIR. ASIR had a statistically significantly (P= 0.048) lower CTDIvol (9.57±1.08) than the conventional FBP (13.71±3.45), with the use of ASIR, ED were slight differ compared with FBP, the